Charles de Gaulle's legacy of ideas - Rowland, Benjamin M. (Lexington Books, 2011)
Charles de Gaulle combined the skills to master the politics of his own day with an uncanny sense of where history was going and how to position France accordingly. The essays in this volume examine certain of the policies and themes de Gaulle pursued nationally, in the European region, and internationally, giving consideration to their significance in his own time, and today.